2012
DOI: 10.1289/ehp.1205383
|View full text |Cite
|
Sign up to set email alerts
|

Triflumizole Is an Obesogen in Mice that Acts through Peroxisome Proliferator Activated Receptor Gamma (PPAR γ )

Abstract: Background: Triflumizole (TFZ) is an imidazole fungicide used on many food and ornamental crops. TFZ is not thought to be particularly toxic or carcinogenic, but little is known about its effect on development. TFZ is identified as a peroxisome proliferator activated receptor gamma (PPARγ) activator in ToxCast. Because PPARγ is a master regulator of adipogenesis, we hypothesized that TFZ would activate PPARγ, thereby inducing adipogenesis and weight gain in vivo.Objectives: We sought to test the ability of TFZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 41 publications
1
50
0
1
Order By: Relevance
“…Results from these studies, coupled with the facts that a growing number of environmental contaminants are being recognized as PPARγ agonists (e.g. phthalates, tetrabromobisphenol A, triflumizole) 43, 60, 61 and that other toxicants (e.g. lead, arsenic, alcohol, dioxin) suppress osteogenesis via PPARγ-independent mechanisms, 27, 6264 support the hypothesis that environmental exposures could contribute significantly to the pathology of osteoporosis.…”
Section: Discussionmentioning
confidence: 61%
“…Results from these studies, coupled with the facts that a growing number of environmental contaminants are being recognized as PPARγ agonists (e.g. phthalates, tetrabromobisphenol A, triflumizole) 43, 60, 61 and that other toxicants (e.g. lead, arsenic, alcohol, dioxin) suppress osteogenesis via PPARγ-independent mechanisms, 27, 6264 support the hypothesis that environmental exposures could contribute significantly to the pathology of osteoporosis.…”
Section: Discussionmentioning
confidence: 61%
“…A single dose of TBT given to mice prenatally caused the mesenchymal stem cell population in offspring to veer towards the adipose lineage at the expense of bone 41 . When mice were exposed to triflumizole in the water throughout pregnancy, mesenchymal stem cells preferentially differentiated into adipocytes in a PPARγ-dependent process 73 . Prenatally TBT-treated animals had more and larger fat cells and substantial fat accumulation in the liver 50 .…”
Section: Developmental Origin Of Adipose Tissue and Susceptibility Tomentioning
confidence: 99%
“…One way to minimize EDC exposure is to consume organic fruits, vegetables and grain products insofar as possible. An increasing number of fungicides routinely applied to fruits and vegetables are being identified as obesogens and metabolic disruptors 73, 102 and the levels of agrochemical residues such as glyphosate on corn, wheat and rice continues to rise 103 . It may also be reasonable to recommend that women minimize the use of cosmetics and personal care products containing EDCs (such as parabens and phthalates).…”
Section: How To Cope With Obesogen Exposurementioning
confidence: 99%
“…We found that treatment with the environmental obesogen, TBT, or the pharmaceutical obesogen, rosiglitazone (ROSI) led to adipogenic differentiation of 3T3-L1 preadipocytes in vitro and prenatal exposure of pregnant mice to these chemicals led to increased fat deposition at birth [30]. The widely used fungicide, triflumizole, also promoted adipocytic differentiation and gene expression in MSCs and 3T3-L1 cells; this effect disappeared when cells were treated with triflumizole in the presence of a PPARγ antagonist [69]. Prenatal TBT or ROSI exposure induced cultured naive MSCs to differentiate into adipocytes in a PPARγ-dependent manner; prenatal exposure of laboratory animals to TBT or ROSI significantly enhanced commitment of MSCs isolated from bone marrow or adipose tissue to the adipogenic lineage at the expense of the osteogenic lineage [44].…”
Section: Edcs and Reprogramming Of Msc Fatementioning
confidence: 99%
“…The obesogen hypothesis is still relatively new and there is a dearth of research in this area, particularly with regard to mechanisms, developmental time windows, and interactions with diet. Our published work showed that PPARγ activators such as TBT and triflumizole modulate critical steps of adipogenesis in vitro and in vivo though RXR/PPARγ and that prenatal exposure to these obesogens predisposes MSCs to become adipocytes by epigenetic imprinting into the memory of the MSC compartment [44,69]. Our recent studies showed that the effects of prenatal TBT exposure are transgenerational; exposure of pregnant F0 animals to environmentally-relevant levels of TBT produced obesogenic effects that persisted through at least the F3 generation [31].…”
Section: Significance and Future Prospectsmentioning
confidence: 99%